The star zoo - Gilbert, Harry (Oxford Univ. Press, 1996)
In the far distant future, Hummingbird is a girl of sixteen who lives somewhere in the Galaxy, on the planet called Just Like Home. She has the name "Hummingbird" in big letters on all her clothes, but she has never seen a real hummingbird. She has never seen any living animal or bird at all. The Book of Remembering says that there were once many animals on a planet called Earth, but that was before the Burning, a long, long time ago...